Customer Complaint Analysis Using Hadoop (Consumer Analysis) (International Journal of Engineering and Computer Science, 2017)
Customer complaint Analysis is Handling Customer Dissatisfaction. It may accompanies Web customer complaint management, This may be a critical Issue for the Customer. In this paper we are going to Investigate the current sources of customer complaints and what are the causes of complaints and want to seek the effective ways of handling customer complaints by examining different type of products and Issues. For achieving customer complaint analysis we are using Big data platform for storing of huge amount of Data. These data are stored in the form of traditional Database. Big data mainly focus on the storage of data. It majorly focuses on three attributes they are Data Volume, Data Velocity and Data Variety.